Exotic Options and Hybrids : a Guide to Structuring, Pricing and Trading. - Bouzoubaa, Mohamed (John Wiley & Sons, 2010)
Toxic waste ... it is a sad day when derivatives are described as toxic waste. Are these financial products really so, particularly those of exotic nature, or is it in fact people's grasp and usage of them that is the source of toxicity? While the use of derivatives increased in recent years at astounding rates, the crash of 2008 has revealed that people's understanding of them has not rivalled their spread. Exotic Options and Hybrids is the first book to guide practitioners on how to structure, price and trade modern exotic and hybrid derivatives, without complicating matters with the use o.